Cover crops effects on soil hydraulic properties in two contrasting Mollisols of Argentinean Pampas region - Villarreal, Rafael (2022)
Decreasing of physical quality of Mollisols in the Argentinean Pampas region is observed due to simplified crop rotations. The main objective of this work was to evaluate the effects of cover cropping management on soil water capture, transport and storage as compared with different crop rotations with bare fallow in two different and representative Mollisols of Argentinean Pampas region (one Typic Argiudoll (TA) and one Typic Hapludoll (TH)). Water capture, transport and storage processes were assessed through soil sorptivity, infiltration tests at different pressures heads and soil water retention curve (SWRC) determinations. In addition, aggregate stability and soil organic carbon (SOC) were determined and the relationship between studied variables and processes was evaluated. It was observed that soybean monocultures jeopardize Mollisols conservation, decreasing water capture and transport and SOC content. The inclusion of cover cropping management increased the soil water transport in the TA and water capture in the TH, as compared to bare fallow rotations. In this sense, our results show that cover cropping could be a suitable management in order to recover degraded soils due to simplified crop rotations in Mollisols from the Argentina Pampas region.